EVALUASI POTENSI UNIT PRODUKSI DALAM PEMBINAAN JIWA WIRAUSAHA SISWA DAN GURU SMK - Sutopo, Adi (TABULARASA, 2014)
This study aims to reveal how the implementation of the existing production Vocational Services Unit (VSU), include: 1) implementation of the VSU to improve the students competence; 2) implementation of the VSU as a means of learning and entrepreneurship, for students and teachers as well as provide operational support school. This study is the evaluation of the CIPP model and Logic models. The study population was a Vocational Technology in DIY and samples taken by purposive sampling, include: SMKN 2 Jetis Yogyakarta; SMKN 2 Depok Sleman; SMKN 2 Kulon Progo and SMKN 2 Wonosari Gunung Kidul. Retrieval and quantitative data collection using questionnaires, while the qualitative data using interviews, in-depth observation and documentation. Quantitative data analysis using descriptive analysis, while qualitative analysis using a model of Miles and Huberman. The results showed bahwaVSU at SMK DIY able to build entrepreneurship in the form of: (a) human resource management and sarpras in school for business activities, (b) the operational contribution that the contribution of electricity costs, maintenance tools wear out, and the addition of supporting tools and the main to practice/production services, (c) add to the welfare of the school community in the form of additional honoraria for implementers, giving holiday allowance for all teachers and employees; (d) establish cooperative relationships with industry.